Two-liquid stratified electroosmotic flow in microchannels - Gao, Yandong (2008)
Two-liquid stratified electroosmotic flows are analyzed analytically and numerically. The model considers surface charges at the interface, which induce jumps of both pressure and stress across the interface. A method to control the interface position using electroosmosis is provided. This study provides insights into the two-liquid electroosmotic flow in microchannels.